The impact of spaced learning within physics lessons in secondary schools - Yuxi Zhou; Rachel Hartley; Alessio Bernardelli; Andrew Tolmie (PLoS ONE, 2025)
Spaced learning (SL) involves distributed learning with timed distraction breaks unrelated to the learning input. These breaks are thought to facilitate consolidation of novel information in long-term memory by accommodating post-activation neural recovery and biochemical changes in potentiation. Applications of SL have become commonplace across UK teaching and feature in government guidance, although there have been few research trials, especially within secondary schools, and none addressing physics independently. However, past research with 14–16-year-old students in England found that interspersing a fast-paced video input with ten-minute distraction breaks in a standard hour-long biology lesson yielded exam performance equivalent to regular teaching across many months. The present study adapted this regime to learning a novel physics topic, atomic structure, including radioactive decay, part of pre-16 compulsory science education in England. An in-class video covered all of the subject content in a single one-hour lesson, with three learning inputs, of length 11 - 14 minutes, interspersed with ten-minute distraction breaks. As well as ‘business as usual’ controls, the research included groups that only experienced the SL lesson, and those who were exposed to it prior to traditional teaching. Impact on learning was assessed using tests similar to state examinations taken at the end of a two-year physics course. Six non-selective state (non-fee charging) schools with varying demography were invited to join the study to ensure the sample was representative of the 93% of students who attend such schools in England. In total, 336 students completed all pre- and post-intervention (immediate and delayed) tests. Students studying combined sciences and separate physics were divided into groups cutting across conditions, with the former taking a shorter test. SL led to immediate benefits for separate physics students, but the SL only group showed no further gain at delayed post-test, with performance then equal to controls, as in past work. However, the SL plus group exhibited additional gains, 50% to 90% greater than the other groups at delayed post-test, following traditional teaching. Among combined science students, the SL plus group showed gains at delayed post-test 60% greater than controls. These effects were consistent across different schools. The implication is that SL provides a foundation for subsequent learning, often doubling its efficiency regardless of context, and that it does so with minimal additional input.